Expression and clinical value of EIF3CL in serous ovarian cancer - Tingting Li; Longyang Liu; Qudi Qiao; Zhongqiu Lin; Jianhuan Yuan; Zhaoyang Zeng; Jilong Yao (Journal of International Medical Research)
Objectives This study aimed to explore the expression of eukaryotic translation initiation factor 3 subunit C-like in serous ovarian cancer samples (both paraffin-embedded and fresh samples) and evaluate its clinical value in patients with serous ovarian cancer. Methods Twenty-five fresh serous ovarian cancer tissues and their paired paratumor tissues were subjected to reverse transcription–quantitative polymerase chain reaction assay to detect eukaryotic translation initiation factor 3 subunit C-like messenger RNA expression. In addition, 135 paraffin-embedded serous ovarian cancer samples and 36 paratumor samples were assessed for eukaryotic translation initiation factor 3 subunit C-like protein expression using immunohistochemistry. Results Both protein and messenger RNA expression levels of eukaryotic translation initiation factor 3 subunit C-like were higher in serous ovarian cancer samples than in paratumor samples, and its high expression was associated with poor overall survival in patients with serous ovarian cancer. In addition, multivariate Cox regression analysis showed that high expression of eukaryotic translation initiation factor 3 subunit C-like was an independent poor prognostic factor for patients with serous ovarian cancer. Conclusions Eukaryotic translation initiation factor 3 subunit C-like is upregulated in serous ovarian cancer samples, and it may be recommended as a useful poor prognostic biomarker in patients with serous ovarian cancer.